Molecular dynamics simulations of shock-induced plasticity in tantalum - Tramontina Videla, Diego Ramiro (2013)
We present Non-Equilibrium Molecular Dynamics (NEMD) simulations of shock wave compression along the [001] direction in monocrystalline Tantalum, including pre-existing defects which act as dislocation sources. We use a new Embedded Atom Model (EAM) potential and study the nucleation and evolution of dislocations as a function of shock pressure and loading rise time. We find that the flow stress and dislocation density behind the shock front depend on strain rate. We find excellent agreement with recent experimental results on strength and recovered microstructure, which goes from dislocations to a mixture of dislocations and twins, to twinning dominated response, as the shock pressure increases.